PENYULUHAN AGAMA BAGI KOMUNITAS MASYARAKAT ADAT KEJAWEN DI KABUPATEN BANYUMAS - Arnis Rachmadhani (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
This qualitative research was conducted in the indigenous javanese communities at Pekuncen village Jatilawang District of Banyumas Regency. Data was collected through interviews, observation, documentation, and FGD. This research describes the spread of traditional Javanese by Ki Bonokeling which has a variety ofrituals such as unggahan and udunan can be an inspiration for the instructor of religion to build or strengthen faith in religious harmony.Although the presence of the instructor of religion have not optmal yet in entering the religius coaching space in indigenous communities because still found some problems are: structural problems, problems of guidance materials, coaching strategies effectiveless, and religious harmony issues.